Is there an increase in the incidence of uterine carcinosarcoma in north-east Scotland? A 19 years population-based cohort study. Issue 2 (May 2013) - Gurumurthy, M; Lahiri, R; Scott, N; Miller, I; Cruickshank, ME; Parkin, DE
Background and aims: The incidence of uterine carcinosarcoma and factors associated with its survival are little known and this study helps to address this question for women residing in north-east Scotland. Methods and results: Data were collected from women diagnosed with carcinosarcoma of the uterus residing in north-east of Scotland from 1991 to 2009. Kaplan–Meier plots and Cox regression analysis were used for analysis. A total of 43 women were analysed during this period. The median survival was 25 months. The estimated five-year survival for stage I/II disease was 52.5% (95% CI: 30.5–74.5%). The 2-year survival rate for stage III/IV disease was 46% (95% CI: 16–75%). There was an increase in the incidence during this period. Improved survival was seen in early-stage disease (FIGO stages I and II) and in the absence of lymphovascular space invasion (LVSI; p = 0.015). A total of 26% of the women had a history of tamoxifen usage with no effect seen on survival. Multivariate analysis showed that when treatment modality and LVSI were adjusted for FIGO staging, there was no statistical significance in the survival outcomes. Conclusion: The incidence of uterine carcinosarcomas is increasing parallel with endometrial carcinomas with no significant effect of tamoxifen on survival.